HIV Infection in Attendees of Psychiatric Clinics in Harare, Zimbabwe; Prevalence, Associated Factors and HIV Care Uptake - Madziro-Ruwizhu, Tatenda B; Nyagura, Tendai; Takarinda, Kudakwashe; Jack, Helen E; Kajawu, Lazarus; Mangezi, Walter (Springer New York LLC, 2021)
Determination of HIV prevalence among people with mental illness is necessary for developing integrated services for HIV and mental illness. This study determined HIV prevalence and uptake of HIV care among outpatients of psychiatric hospitals in Harare, Zimbabwe. HIV status was determined using open testing of 270 randomly selected consenting adult outpatients. HIV prevalence was 14.4% and the risk of acquiring HIV was similar to the general population of adults in Zimbabwe. Females were six times more likely to have HIV infection than males. Although a relatively high proportion of patients had been tested for HIV in the past (77.2%), fewer were recently tested (27.8%). Access to HIV care was high (94%) amongst patients previously diagnosed to be HIV positive. Tertiary mental health services should offer similar HIV care packages as other points of care and there is need for interventions that reduce the risk of HIV in women with mental disorders.